The utilization of international humanitarian law and, in particular, the Geneva Convention Treaty Régime, to deter acts of international terrorism, with special reference to armed struggles by "Peoples" for their right to self-determination - Chadwick, Elizabeth (1994)
In 1937, the international community preliminarily agreed on a definition of international terrorism. A major World War and Cold War since that time have made impossible any such modern consensus. In particular, the U.N. principles of the equal rights and self-determination of "Peoples" have caused political and juridical confusion in that liberation fighters who utilize terror methods as one tactic in an overall political strategy to achieve self-determination are frequently termed "terrorists", and prosecuted as such.